The Returns to Cognitive Abilities and Personality Traits in Germany - Guido Heineck; Silke Anger (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We provide the first joint evidence on the relationship between individuals' cognitive abilities, their personality and earnings for Germany. Using data from the German Socio-Economic Panel Study, we employ scores from an ultra-short IQ-test and a set of measures of personality traits, namely locus of control, reciprocity and all basic items from the Five Factor Personality Inventory. Our estimates suggest a positive effect of so-called fluid intelligence or speed of cognition on males' wages only. Findings for personality traits are more heterogeneous. There however is a robust wage penalty for an external locus of control for both men and women.
Keywords: J24; J31; I21; 330; Cognitive abilities; personality traits; Five Factor Model; Locus of control; reciprocity; wages